Vulva Hygiene Dan Konsumsi Telur Terhadap Laserasi Perineum Ibu Nifas Puskesmas Susukan 1 Banjarnegara - lukita candra maharani; Feti Kumala Dewi; Surtiningsih Surtiningsih (PT.Mantaya Idea Batara, 2025)
Perineal laceration is a tear that occurs when a baby is born either spontaneously or by using tools or procedures. This tear occurs in almost all primiparas. Healing of laceration wounds is by implementing vulva hygiene and consuming chicken eggs. Birth data at the Susukan 1 Banjarnegara CommunityHealth Center, the number of births was 11 mothers gave birth and 6 of them received perineal lacerations, grade 2 lacerations, mothers complained of pain in the perineal area causing difficulties. defecation (defecation), fear of mobilization, and lack of knowledge which believes that culture is hereditary due to the myth of taboos for postpartum mothers who are not allowed to eat fishy food such as eggs. This method uses a subsidence scale instrument and a knowledge questionnaire, the number of respondents used is 5 respondents whoexperienced grade II perineal lacerations at the Susukan 1 Banjarnegara Community Health Center. The average perineal laceration of postpartum mothers was grade II as many as 5 respondents and the age of the five respondents was 20-33 years with the previous average condition of the woundas seen by the reeda score being 3, experiencing increased wound healing after the application of vulva hygiene and consumption of chicken eggs for 5 consecutive days became a score of 0 with an average decrease of 2.4 and the knowledge of the five respondents increased to good after the application of vulva hygiene and consumption of chicken eggs. The conclusion of this case study was that vulva hygiene and Consuming chicken eggs is effective in healingperineal lacerations